2015
DOI: 10.1155/2015/983978
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Different Test Combinations for Diagnosis ofMycobacterium aviumSubspeciesparatuberculosisInfecting Dairy Herds in India

Abstract: A total of 355 cows were sampled (serum, n = 315; faeces, n = 355; milk, n = 209) from dairy farms located in the Punjab state of India. Faeces and serum/milk samples were screened by acid fast staining and “indigenous ELISA,” respectively. IS900 PCR was used to screen faeces and milk samples. Bio-load of MAP in dairy cows was 36.9, 15.6, 16.3, and 14.4%, using microscopy, serum ELISA, milk ELISA and milk PCR, respectively. Estimated kappa values between different test combinations: serum and milk ELISA, faeca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 39 publications
4
13
0
Order By: Relevance
“…The present findings were in agreement with Garg et al (2015) who also reported good agreement between serum ELISA and faecal PCR and fair agreement between microscopy and faecal PCR in dairy animals. Whereas, Singh et al (2013) reported substantial agreement between "microscopy" and blood PCR.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 93%
See 1 more Smart Citation
“…The present findings were in agreement with Garg et al (2015) who also reported good agreement between serum ELISA and faecal PCR and fair agreement between microscopy and faecal PCR in dairy animals. Whereas, Singh et al (2013) reported substantial agreement between "microscopy" and blood PCR.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 93%
“…Sensitivity depends on the stages of disease within the flock and the antigens used in the serologic test (Hilbink et al, 1994). Present findings were in accordance with Garg et al (2015) who also reported higher sensitivity of ELISA-PCR compared to microscopy-PCR.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 90%
“…In another study, sensitivity and specificity of indigenous ELISA kit was 66.6 and 75.0% and 68.1 and 66.6% with tissue culture and tissue PCR, respectively (Singh et al, 2008). For estimating sensitivity and specificity of ELISA in case of MAP infection is by comparing serum ELISA with fecal culture (Garg et al, 2015). Similar comparative studies were carried out by Singh et al (2009b), where 'Indigenous g-ELISA kit' had superior diagnostic potential and high specificity as compared to commercial ELISA kit.…”
Section: Discussionmentioning
confidence: 99%
“…An AC electrokinetic impedance sensing can be used for rapid and sensitive detection of specific antibodies in serum samples and this could be a basis for development of a point of care diagnostic device for human and bovine tuberculosis (Cui et al, 2013). Garg et al (2015) recently reported that the combination of milk ELISA and milk PCR may be adopted as a model strategy for the screening and diagnosis of JD in lactating cattle herds in Indian conditions.…”
Section: Discussionmentioning
confidence: 99%